De Maria Numquam Satis: The Significance of the Catholic Doctrines on the Blessed Virgin Mary for All People - Gentle, Judith Marie; Fastiggi, Robert L. (Hamilton Books, 2009)
Who is the Blessed Virgin Mary? Why is she significant for all people? How is she at work alongside her Divine Son, Jesus Christ, in redeeming and bringing us into union with the Blessed Trinity in this life and the next? De Maria Numquam Satis considers these and other questions through a collection of essays that explain the primary truths of the Catholic Faith regarding the Blessed Virgin Mary in a way that is at the same time 'ever ancient and ever new.'